2015
DOI: 10.14712/18023061.472
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Awareness and Attitudes Among Adolescents in the Czech Republic

Abstract: The distribution of climate change awareness of Czech adolescent students and their climate change related attitudes are analysed in this study. Even though the influence of accessed information on actual behaviour is usually described as rather small by most experimental studies, we argue that the effect of knowledge on specific behaviour becomes significant in a long time perspective. The main focus of the study is thus to offer a segmentation of youth in the issue of climate change related to information so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
2
6
1
Order By: Relevance
“…However, 84.4% these respondents understood the meaning of global warming. This study agrees with a similar study by Skalík [ 36 ] in Czech Republic where they found that over 80% of participants had climate change awareness.…”
Section: Discussionsupporting
confidence: 93%
“…However, 84.4% these respondents understood the meaning of global warming. This study agrees with a similar study by Skalík [ 36 ] in Czech Republic where they found that over 80% of participants had climate change awareness.…”
Section: Discussionsupporting
confidence: 93%
“…The poor understanding perhaps correlated with their opinion that climate change evidence is not convincing. This result was different from a research in the Czech Republic which identified that more than 80% of research participants (adolescents) had good climate change awareness [23]. Secondly, participants did not recognize that climate change is caused by anthropogenic factors.…”
Section: Discussioncontrasting
confidence: 76%
“…According to the current study's findings, 70% of the participants were knowledgeable about the issue of CC and its effects. These results were based on similar studies conducted in other countries, which revealed that more than 80% of the respondents were aware of the problem of CC and its consequences ( 17 , 23 ). However, the research results contrast with studies conducted in Saudi Arabia, Turkey, and Kenya, which revealed a low level of knowledge about CC among participants ( 24 26 ).…”
Section: Discussionsupporting
confidence: 56%